1998
DOI: 10.1007/s004670050465
|View full text |Cite
|
Sign up to set email alerts
|

Familial ureteral abnormalities syndrome: genomic mapping, clinical findings

Abstract: Abnormal development of the ureter during embryogenesis, when occurring in multiple family members, appears to be a genetically determined defect with autosomal dominant inheritance and high penetrance, which can lead to significant kidney damage, renal failure, and death. We have studied 48 individuals within a large kindred in which ureteral-related abnormalities (including vesicoureteral reflux, ureteropelvic junction obstruction, duplicated ureters, and medullary sponge kidney) were segregated. Family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Because VCUG is an invasive test, our study could not recommend this procedure to determine whether these two patients had concurrent VUR. Nevertheless, these two individuals were considered as affected because UPJ obstruction is a clear abnormality, and previous studies have suggested that VUR and UPJ obstruction have a common genetic cause (4,21). Affected individuals had no evidence of secondary causes of VUR or syndromic abnormalities.…”
Section: Patientsmentioning
confidence: 99%
“…Because VCUG is an invasive test, our study could not recommend this procedure to determine whether these two patients had concurrent VUR. Nevertheless, these two individuals were considered as affected because UPJ obstruction is a clear abnormality, and previous studies have suggested that VUR and UPJ obstruction have a common genetic cause (4,21). Affected individuals had no evidence of secondary causes of VUR or syndromic abnormalities.…”
Section: Patientsmentioning
confidence: 99%
“…Several renal and urologic malformations including refluxing or obstructive uropathies as well as dysplastic kidneys are commonly found in a familial pattern [3,4]. Nevertheless, only two descriptions of familial crossed renal ectopia have previously been published.…”
Section: Discussionmentioning
confidence: 99%
“…Hydronephrosis is not uncommonly part of several congenital syndromes and has been described in families, mainly in siblings and with few affected members for up to three generations [4]. Familial cases may be more common than is clinically evident: Ultrasound examinations in smaller studies have shown that approximately 50% of siblings are affected [5].…”
Section: Hydronephrosismentioning
confidence: 98%